Focus on developing al-Qur'an learning methods in Indonesia: learning style approach - Thoifah, Ianatut; Yusuf, Muhammad; Khosim, Nanang (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
This research aims to analyze the focus of developing Al-Qur'an learning methods with a learning style approach and the achievements of Al-Qur'an learning methods. The research approach uses a qualitative approach and is of the metasynthesis type. Collecting data to answer the existing problem formulation, researchers analyzed learning method guidebooks totaling 7 trends in Al-Qur'an learning methods, articles from journals, and other supporting books. The results of this research indicate that the focus of the development of trends in Al-Qur'an learning methods in Indonesia is more towards audio and visual learning styles. The achievements of the trend in Al-Qur'an learning methods in Indonesia can be seen from the ability to read the Al-Qur'an in tartil, understand gharib and the basics of recitation; knowing random hijaiyah letters, memorizing the Koran, especially short letters; makhraj, and writing Arabic letters. It can be concluded that each method has similarities in developing methods with an audio and visual learning style approach, while the differences between each method can be seen in the achievement of Al-Qur'an learning indicators, but each method has not shown results.